2016
DOI: 10.1111/acel.12462
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol ameliorates age-associated loss of fibroblast function by attenuating IFN-γ/STAT1-dependent miR-7 upregulation

Abstract: SummaryAge‐related defects in fibroblast differentiation and functionality were previously shown to be associated with impaired hyaluronan (HA) synthase 2 (HAS2) and epidermal growth factor receptor (EGFR) function, as a result of upregulated microRNA‐7 (miR‐7) expression. In aging fibroblasts, inhibiting miR‐7 prevented the dysregulation of the HA‐mediated CD44/EGFR signaling pathway. Here, we investigated transcriptional upregulation of miR‐7 and implicated the age‐associated over‐activation of JAK/STAT1 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 41 publications
(50 reference statements)
1
43
0
Order By: Relevance
“…The influence of estrogen on wound healing was investigated in the animal model in 1947 [ 50 ] and in humans in 1953 [ 51 ]. Afterwards, much evidence supports that the estrogen is important on wound healing [ 31 , 41 , 42 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. It has been shown that primary estrogen deficiency contributes to cutaneous aging and delayed wound repair or impaired wound healing [ 41 , 42 ].…”
Section: Estrogen Signaling and Wound Healingmentioning
confidence: 99%
“…The influence of estrogen on wound healing was investigated in the animal model in 1947 [ 50 ] and in humans in 1953 [ 51 ]. Afterwards, much evidence supports that the estrogen is important on wound healing [ 31 , 41 , 42 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. It has been shown that primary estrogen deficiency contributes to cutaneous aging and delayed wound repair or impaired wound healing [ 41 , 42 ].…”
Section: Estrogen Signaling and Wound Healingmentioning
confidence: 99%
“…Different aspects have to be considered when explaining this discrepancy between in vivo and in vitro results especially for miR‐7. On the one hand, other factors regulating the miR‐7 expression have been described, for instance INF‐γ or oleic acid . The in vitro experiments were performed in the absence of fetal calf serum (FCS) which is different from the situation in vivo , were many cytokines or growth factors are present.…”
Section: Discussionmentioning
confidence: 72%
“…On the one hand, other factors regulating the miR-7 expression have been described, for instance INF-γ or oleic acid. 48,49 The in vitro experiments were performed in the absence of fetal calf serum (FCS) which is different from the situation in vivo, were many cytokines or growth factors are present. Since it is known that cytokines affect the expression of miRNAs, it was tried to minimize the impact of these factors on the results of the in vitro experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using mutant cell lines and knockout mice have shown that STAT1 plays a significant role in interferon (IFN)-γ and IFN-α/β mediated signaling. The activity of STAT1 is tightly regulated by multiple mechanisms including post-translational modification, regulatory proteins and modulation by other STAT family members (1315). In a previous study, it was shown that (16) miR-146a can influence STAT1 activity via multiple pathways.…”
Section: Discussionmentioning
confidence: 99%